Mar del Plata vertical Piqueta, construcción y progreso. - Ortiz, Bruno (Estudios de Teoría Literaria, 2025)
The article focuses on the work "Mar del Plata Vertical: Piqueta, Construction, and Progress" by Víctor Pegoraro, which explores the history of construction in Mar del Plata from the 1930s to 1975. The author, a researcher at CONICET, analyzes how the construction boom transformed the city, facilitating access to housing through the Horizontal Property Law of 1948 and reflecting a change in social and economic dynamics. The work is divided into three chapters that address the urban context, real estate activity, and the consequences of construction and demolition on the city's identity. Pegoraro invites reflection on the impact of these processes on cultural heritage and the society of Mar del Plata.